(3GdSdhc GdJfXjej hGOGQI GdehGQO GdHTQjI (B/s - (3Mfaj, YHO GdZaGQs ((3GdGScfOQjI(B: s (3OGQ GdLGeYI GdLOjOI ddfTQ(B, s, 2002)
(3JYJHQ GOGQI GdCaQGO MdbI GdGJUGd GdOGFe Hjf GdGOGQI hGdYeGd ef fGMjI hHjf GdEOGQI hGdfbGHI ef fGMjI CNQi , agj JYed Ydi JOYje hJhKjb GdYdGbI eY GdfbGHI dG jbJUQ GdfTGW YfO gPG GdMO hOGFeG CjVG dG HO ef GdUjGfI hGdeMGaXI Ydi Gdbhi GdHTQjI ef Cj CNWGQ JJgOOge aj HjFI GdYed eeG jJWdH Ndb GdHjFI hGdefGN GdfaSj GdedGFe ddCOGA eeG jchf dg GKGQ Ydi GdGfJGLjI jJWdH GdGeQ CjVG OQGSI OhGaY GdCaQGO hGdJYQa Ydi eONd GdJCKjQ Ydi GdSdhc GdCaQGO hJWhjYg HeG jJfGSH hGdSdhc GdJfXjej JWdH GdCeQ deYGdLI gPG GdehVhY JbSjeg Edi KdGKI CHhGH MjK ENJU GdHGH GdChd Edi OQGSI GdhXGFa hGdeeGQSGJ GdJTZjdjI ddGOGQI hGdCaQGO HGdefXeGJ , HjfeG JYQV GdLRA GdKGfj ddOGaYjI hSdhc GdCaQGO HGdefXeI hGNJU GdLRA GdKGdK HGdCef hGdSdGeI aj HjFI GdYeds
Keywords: (3GOGQI ehGQO HTQjI (B- (3Sdhc JfXjejs